Gallotannin derivatives from mango (Mangifera indica L.) suppress adipogenesis and increase thermogenesis in 3T3-L1 adipocytes in part through the AMPK pathway. (July 2018) - Fang, Chuo; Kim, Hyemee; Noratto, Giuliana; Sun, Yuxiang; Talcott, Stephen T.; Mertens-Talcott, Susanne U.
Graphical abstract: Highlights: Gallotannin derivatives of mango (MG and PG) inhibit adipogenesis of 3T3-L1. PG exerts thermogenic activity by up-regulating UCP1 and Sirt1. Anti-obesity activity of PG is partly attributed to the activation of AMPK pathway. MG and PG prevent TNF-α-induced ROS production. Abstract: Expansion of adipose tissue in obesity is associated with dysregulation of adipokines, which can lead to long-term metabolic disorders. Gallotannin derivatives from mango possess anti-inflammatory activities, but their potential role in lipid metabolism is not well investigated. In this study, 3T3-L1 preadipocytes were differentiated into adipocytes and treated with mango polyphenols (MG), or pyrogallol (PG) for 6 days. The anti-adipogenic activity of PG was demonstrated by reduced number of lipid droplets and expressions of adipogenic markers, such as peroxisome proliferator-activated receptor γ (PPARγ) and CCAAT/enhancer binding protein α (C/EBPα). In mature adipocytes, PG promoted adipocyte browning and increased the expressions of uncoupling protein 1 (UCP1) and sirtuin 1 (Sirt1). Knockdown of AMP-activated protein kinase (AMPK) α1 with siRNA partially abolished the effect of PG on adipogenesis. Results indicate that gallotannin derivatives modulate lipid metabolism, at least in part, though the AMPK pathway, and possess potential to prevent obesity-related conditions.